RANCANG BANGUN PENGISIAN AKI LISTRIK PORTABEL DAN AKI SHS DENGAN AUTOMATIC SWITCH - Bastian Wicaksono; Akhmad Zainuri; Muhammad Fauzan Edy Purnomo (Jurnal Mahasiswa TEUB, 2022)
This study designed a device that is charging portable electric batteries and SHS batteries with automatic switches that will be used on the beach at Clungup Mangrove Conservation (CMC) for electricity needs in the area. In the design, the energy sources will be stored in portable electric batteries and SHS batteries. SHS batteries will be placed in the command post area from the CMC beach and portable electric batteries will be used at the post and at the CMC beach. The voltage source comes from solar panels that capture sunlight. Solar charge controller (SCC) is an electronic device that functions as control and monitoring of voltage, current, and temperature. SCC will prevent overcharging of SHS batteries and portable electric batteries. In its implementation, portable electric batteries and SHS batteries will experience low or high voltage level conditions. The automatic switch system will work if three conditions occur. The first condition is when the electric battery has a lower voltage level than the SHS battery, the SCC connected to the relay will be active and charge the portable electric battery. The second condition is that if the portable electric battery